Investigating the urban heat and cool island effects during extreme heat events in high‐density cities: A case study of Hong Kong from 2000 to 2018. (1st June 2021) - Ren, Chao; Wang, Kai; Shi, Yuan; Kwok, Yu Ting; Morakinyo, Tobi Eniolu; Lee, Tsz‐cheung; Li, Yuguo
Abstract: Urban heat island (UHI) and cool island (UCI) effects are well‐known and prevalent in cities worldwide. An increasing trend of extreme heat events has been observed over the last few decades and is expected to continue in the foreseeable future. In this study, warm periods (May to September) of 2000–2018 were examined to acquire a comprehensive understanding of the UHI and UCI characteristics for the case study of Hong Kong, China. Twenty‐two weather stations in Hong Kong were classified into four categories, namely urban, urban oasis, suburban, and rural, with reference to the local climate zone (LCZ) scheme, to analyze UHI and UCI phenomena during extreme heat and non‐extreme heat situations. One representative type of extreme heat events was considered in this study: three consecutive hot nights with two very hot days in between (2D3N). Results show that both the UHI and UCI effects are exacerbated during extreme heat events. Using the concept of the UHI degree hours (UHIdh) and UCI degree hours (UCIdh), their spatial patterns in Hong Kong during extreme heat and non‐extreme heat situations were mapped based on multiple linear regression models. It is found that the predictor variable – windward/leeward index is a significant influential factor of both UHIdh and UCIdh during extreme heat events. The resulting UHIdh and UCIdh maps not only enhance our understanding on the spatial pattern and characteristics of the UHI and UCI during extreme heat events, but could also serve as a useful reference in climate change adaptation, heat‐health risk detection, cooling‐energy estimation and policy making. Abstract : Strengthened daytime urban cool island (UCI) and nighttime urban heat island (UHI) effects are observed in the urban areas of Hong Kong during the extreme heat (EH) events. The spatial pattern of the UHI degree hours (UHIdh) and UCI degree hours (UCIdh) under EH and non‐EH events shows that the compact building clusters of urban areas contribute to the increased UHIdh, especially at nighttime during EH events. It is found that the weakened urban ventilation in the nighttime could cause the intensification of the UHI effect on EH‐days.